Microstructure characterization and strengthening behavior of dual precipitation particles in CuTi microalloyed dual-phase steels. (15th March 2019) - Li, Cheng-Han; Chen, Chih-Yuan; Tsai, Shao-Pu; Yang, Jer-Ren
Abstract: Copper particles that directly nucleated on the interphase precipitated TiC within the ferrite matrix were found in the CuTi bearing dual-Phase (DP) steel after a multistep heat treatment process. The formation of dual precipitates within ferrite grains should be considered a separated phase transformation process because only titanium carbides form initially when austenite undergoes decomposition reaction; subsequently, copper particles heterogeneously nucleate on these carbides. The above separated precipitation behavior leads to a gentle tempering behavior of CuTi microalloyed DP steel. For example, in Cu microalloyed DP steel, the changes in the average Vickers hardness of ferrite and martensite after 9 h of tempering treatment were 165 to 210 and 407 to 278, respectively. However, in the CuTi microalloyed DP steel, the average Vickers hardness of ferrite and martensite increased from 235 to 249 and 339 to 353, respectively, after 9 h of tempering. Fractography analysis revealed the mixed mode fracture characteristic due to the DP steel consisting of soft ferrite and hard martensite. However, fewer brittle-feature cleavage facets were found in the CuTi microalloyed DP steel after 5 h of tempering treatment, indicating the suppression of damage due to ferrite and martensite interface decohesion. Graphical abstract: Unlabelled Image Highlights: Microhardness increased slightly within ferrite and martensite in CuTi steel after tempering treatment. Fracture by decohesion of ferrite/martensite interface can be inhibited in CuTi steel after 5 h of tempering. Two types of precipitates, namely, Cu and TiC, form simultaneously within the ferrite matrix in CuTi steel. Cu particles are mainly heterogeneously nucleated on existing regular TiC particle arrays.